Mental Health Services in the Wake of COVID-19 and Political Unrest in Myanmar - Lin, Tay Zar; Oo, San San (Eximia, 2023)
Myanmar's mental health and well-being have been profoundly impacted by the COVID-19 pandemic and political unrest. The prevalence of reported depressive symptoms and suicidal ideation highlights the imperative need to evaluate mental health access and services throughout the nation. Population anxiety and distress have increased as a result of the pandemic containment measures and political unrest. Access to mental health services is hindered, particularly in rural and minority-populated areas, by outmoded mental health legislation and a lack of trained professionals, as well as by language barriers. For the development of focused interventions and support systems, it is essential to understand the present situation of mental health access. For the promotion of mental health services, government, INGOs, and local communities are required to collaborate. Myanmar can foster resilience and well-being by prioritising mental health and employing comprehensive strategies, resulting in a healthier and more inclusive society for the citizens.